Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/hel.12999
|View full text |Cite
|
Sign up to set email alerts
|

The expression and function of the B7 family in Helicobacter pylori infection and gastric carcinogenesis process

Abstract: Gastric cancer (GC) was the fifth most common cancer and the fourth leading cause of cancer-related deaths worldwide in 2020. 1 In 2010-2014, the 5-year-survival was very high in Korea (69%) and Japan (60%), but in China, it was only 35.9%, 2 where initial asymptomatic development and subsequent nonspecific symptoms result in a diagnosis at advanced stages with a poor prognosis. Assuming that the current incidence rates remain the same, the annual number of new GC cases are predicted to increase from 1.09 mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 143 publications
0
1
0
Order By: Relevance
“…As early as 1998, in vivo studies had demonstrated that gastric epithelial cells (GECs) upregulate the expression of B7 costimulatory molecules (B7-1, B7-2, B7-H1, and B7-H2) during H. pylori infection. This upregulation helps diminish the activity of CD4+ effector T cells and increase Treg cells, thereby modulating the T cell response ( Ye et al., 1997 ; Zhang et al., 2023 ). B7-H2 (ICOS ligand), a recent addition to the B7 receptor family, provides a costimulatory signal upon binding with ICOS, enhancing T cell activity.…”
Section: Evasion Of Adaptive Immunitymentioning
confidence: 99%
“…As early as 1998, in vivo studies had demonstrated that gastric epithelial cells (GECs) upregulate the expression of B7 costimulatory molecules (B7-1, B7-2, B7-H1, and B7-H2) during H. pylori infection. This upregulation helps diminish the activity of CD4+ effector T cells and increase Treg cells, thereby modulating the T cell response ( Ye et al., 1997 ; Zhang et al., 2023 ). B7-H2 (ICOS ligand), a recent addition to the B7 receptor family, provides a costimulatory signal upon binding with ICOS, enhancing T cell activity.…”
Section: Evasion Of Adaptive Immunitymentioning
confidence: 99%